2013
DOI: 10.5604/15093492.1084361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effectiveness of Kinesiology Taping as an Adjunct to Rehabilitation Following Anterior Cruciate Ligament Reconstruction. Preliminary Report

Abstract: BACKGROUND. Kinesiology Taping (KT) is being increasingly more often used in musculoskeletal rehabilitation. The aim of the study was to assess the effect of Kinesiology Taping on rehabilitation outcomes in patients following anterior cruciate ligament (ACL) reconstruction. MATERIALS AND METHODS. The study enrolled 26 patients (16 women and 10 men) aged between 20 and 41 years. The patients were randomly divided into two groups: an experimental group (Group 1), which received Kinesiology Taping, and a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…For the study by Bialoszewski et al [12], we made use of the p-values of a paired t-test comparing follow-up values with baseline values. For the study of Boguszewski et al [13], we could not find sufficient information to compute confidence intervals. For the study by Balki et al [14], the authors provide the mean and standard deviation values on our request.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For the study by Bialoszewski et al [12], we made use of the p-values of a paired t-test comparing follow-up values with baseline values. For the study of Boguszewski et al [13], we could not find sufficient information to compute confidence intervals. For the study by Balki et al [14], the authors provide the mean and standard deviation values on our request.…”
Section: Discussionmentioning
confidence: 91%
“…The trial could not be included in the review since detailed data were not available upon request from the author. An evaluation of the effectiveness was hampered be the fact that only three studies [11,13,22] involved an active comparator, two of them a pneumatic compression system and one manual lymphatic drainage. The study by Bialoszewski et al [12] as the only one comparing kinesiotaping to manual lymphatic drainage as current gold standard suffers from methodologic flaws and lacks a description of the patient population or a comparison of the two groups.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Chinn et al [18] and Deschamps et al [19] reported that taping applied to patients with chronic ankle instability significantly improved stability of the ankle joint and gait. According to Boguszewski et al [20], taping applied to healthy adults significantly augmented the activation and strength of lower-extremity muscles. Furthermore, Ekiz et al [15] and Kim et al [12] found an increase in walking speed after taping of stroke patients in a 10-meter walking test.…”
Section: Discussionmentioning
confidence: 99%
“…Findings showed the diminution of the surgical swelling, and also of the need of pharmacological resources -the analgesic effect was obtained. 22 Kinesiotaping was successfully applied at persons struggling with the chronic pain, whether patients with neurological diseases or of rheumatologic ones. Most often the analgesic and anti-oedematous properties of elastic tapes were emphasized.…”
Section: Discussionmentioning
confidence: 99%